The treaty of Tapihue between certain mapuches lineages and the government of Chile (1825) - Téllez L., Eduardo; Silva G., Osvaldo; Carrier, Alain; Rojas C., Valeska (Cuadernos de Historia, 2011)
The document reproduced here is a photographic copy of theonly printed version of the Tapihue Treaty, signed on January 7, 1825,by the patriot army colonel and commander in chief of the High Frontier,Pedro Barnechea, representing the Government of Chile and the principalchief of the alliance "llanista" Juan Mariluán,. It was the fi rst of severalpeace agreement sheld between the republic and the various lineagesMapuche groups after independence. While the content of the treatyhas circulated before, a visual reproduction of the original form afterbeing published by order of Congress, in the workshops of the NationalPrinting Offi ce, Santiago de Chile, was not available. It is therefore areliable picture of the "offi cial" sponsored by the Chilean legislature.It is preceded by a presentation that explains the history surrounding itsrelease, rediscovery and technical analysis. Likewise, this presentationprovides comments relevant to the legal scope, anthropological andpolitical content. It makes a special refl ection on the political statusacquired through the territory of Araucania, one of the themes of thiswork, derived from Fondecyt project on the development of the Mapuchesociety at the beginnings of the Chilean republic.